Justice in a globalized world a normative framework - Valentini, Laura (Oxford : Oxford University Press, 2011)
Are wealthy countries' duties towards developing countries grounded in justice or in weaker concerns of charity? 'Justice in a Globalized World' offers both an in-depth critique of the most prominent philosophical answers to this question, and a distinctive approach for addressing it.
Also issued in print format.
Description based on online resource; title from PDF title page (viewed on Jan. 21, 2012).
Includes bibliographical references and index.
Keywords: Economic assistance -- Philosophy; Social justice